Sensory profile & consumer acceptability of sweet cherries - Revell, Joseph M. (2009)
The main objective of this study was to identify key drivers underlying consumer preference and acceptability of sweet cherries. This was achieved using a Flash Profile to identify the sensory diversity perceived providing sensory descriptions of a range of cherry varieties. Various preliminary experiments were performed to optimise the Flash Profile technique prior to the final experiment. In order to perform the final Flash Profile, six varieties of cherry were selected by Norton Folgate Ltd. and assessed by a panel of 12 assessors who all had sensory experience, but not with sweet cherry products. The Flash Profile results showed discrimination between the sweet cherries which was dominated by appearance, but texture and flavour appeared to have an influence. The same sweet cherry varieties were then put through a consumer preference test using a rank-rating method, where products were ranked in order of preference first, followed by a rating exercise to determine liking or disliking using the LAM scale. An internal preference map was generated using this data and this was extended by adding the Flash Profile and some analytical data to the map as supplementary data. The outcome was that flavour intensity and juiciness appeared to be key factors behind preference and acceptability of sweet cherries.